Analysis and functional consequences of increased Fab-sialylation of intravenous immunoglobulin (IVIG) after lectin fractionation. - Fabian Käsermann; David J Boerema; Monika Rüegsegger; Andreas Hofmann; Sandra Wymann; Adrian W Zuercher; Sylvia Miescher (PLoS ONE, 2012)
It has been proposed that the anti-inflammatory effects of intravenous immunoglobulin (IVIG) might be due to the small fraction of Fc-sialylated IgG. In this study we biochemically and functionally characterized sialic acid-enriched IgG obtained by Sambucus nigra agglutinin (SNA) lectin fractionation. Two main IgG fractions isolated by elution with lactose (E1) or acidified lactose (E2) were analyzed for total IgG, F(ab')(2) and Fc-specific sialic acid content, their pattern of specific antibodies and anti-inflammatory potential in a human in vitro inflammation system based on LPS- or PHA-stimulated whole blood. HPLC and LC-MS testing revealed an increase of sialylated IgG in E1 and more substantially in the E2 fraction. Significantly, the increased amount of sialic acid residues was primarily found in the Fab region whereas only a minor increase was observed in the Fc region. This indicates preferential binding of the Fab sialic acid to SNA. ELISA analyses of a representative range of pathogen and auto-antigens indicated a skewed antibody pattern of the sialylated IVIG fractions. Finally, the E2 fraction exerted a more profound anti-inflammatory effect compared to E1 or IVIG, evidenced by reduced CD54 expression on monocytes and reduced secretion of MCP-1 (CCL2); again these effects were Fab- but not Fc-dependent. Our results show that SNA fractionation of IVIG yields a minor fraction (approx. 10%) of highly sialylated IgG, wherein the sialic acid is mainly found in the Fab region. The tested anti-inflammatory activity was associated with Fab not Fc sialylation.